Publishing with Tree-Media: Arbo-real Aesthetics, Pedagogical Ruptures (Revue D’études Interculturelles De L’image, 2025)
In response to the ecological and epistemic crises of the Capitalocene, this paper examines how eco-artist Thijs Biersteker develops tree-media—sensor-driven AI installations that treat trees and fungi not as metaphors or data sources, but as co-authors of environmental knowledge. Through the concept of arbo-real aesthetics, the paper proposes an elemental model of publishing rooted in multispecies reciprocity, latency, and refusal. Biersteker’s installations resist extractive AI paradigms by staging alternative epistemologies grounded in vegetal sensing, seasonal rhythms, and symbiotic time. Analyzing six installations produced between 2018 and 2024, the paper theorizes how these works enact a compostable media logic—one that unsettles mastery and reimagines publishing as a sensory, ethical, and relational process. Rather than offering techno-utopian solutions, the installations inhabit the Promethean paradox: they critique digital extractivism while operating within its constraints. As a prescriptive intervention, the paper introduces Listening with Trees, a three-day pedagogical prototype that speculatively translates these insights into multispecies publishing practices. By publishing with trees—through slowness, decay, and co-authorship—this model offers a low-carbon, speculative alternative to academic and AI-driven knowledge systems in the age of the Chthulucene.